Entrepreneurial mindset and the role of universities as strategic drivers of entrepreneurship: Evidence from the United Arab Emirates. Issue 1 (20th February 2017) - Jabeen, Fauzia; Faisal, Mohd. Nishat; I. Katsioloudes, Marios
Abstract : Purpose: The purpose of this paper is to provide insight into the factors that influence the mindset of youth in the United Arab Emirates (UAE) in choosing entrepreneurship as their future employment. It also suggests the pathway to improve the role of the universities as strategic drivers in inducing an entrepreneurial mindset. Design/methodology/approach: An exhaustive literature review of extant research followed by an exploratory study was conducted. Furthermore, to understand factors influencing the role of universities, interpretive structural modelling methodology is applied to evolve a hierarchy-based relationship among the strategic factors. Findings: The results of empirical research suggest that young people in the UAE rank entrepreneurship as their first employment choice. However, most of them have not attended any formal entrepreneurship-related course in school or in college. The study also suggests that individual and environmental factors influence the entrepreneurial mindset of both males and females in the UAE. The structural model developed in the study indicates that to give an impetus to the entrepreneurial mindset, the government must create a supporting environment with UAE universities playing the role of a catalyst. Practical implications: Professional entrepreneurship instruction is seen as a strategic tool to stimulate financial and societal growth. The results could provide insights for both entrepreneurship educators and policymakers and will boost their commitment to promote the entrepreneurial mindset within UAE society by enhancing and developing traits associated with entrepreneurial success. The results support recognition of the factors that induce educational programmes and economic incentives targeted at the development of sustainable entrepreneurial culture and ventures in the UAE. Originality/value: The study is an effort to highlight the role of higher education in envisaging and cultivating entrepreneurs in a fast-growing developing country through a survey and a hierarchy-based model.